2014
DOI: 10.1002/cssc.201402314
|View full text |Cite
|
Sign up to set email alerts
|

High Shear Homogenization of Lignin to Nanolignin and Thermal Stability of Nanolignin‐Polyvinyl Alcohol Blends

Abstract: A new method to prepare nanolignin using a simple high shear homogenizer is presented. The kraft lignin particles with a broad distribution ranging from large micron- to nano-sized particles were completely homogenized to nanolignin particles with sizes less than 100 nm after 4 h of mechanical shearing. The (13) C nuclear magnetic resonance (NMR) and (31) P NMR analysis showed that there were no major changes in the chemical composition between the starting kraft lignin particles and the nanolignin obtained af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
135
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(146 citation statements)
references
References 31 publications
7
135
0
2
Order By: Relevance
“…1a shows the TG and DTG curves of pristine lignin and LNPs: compared with pristine lignin, the DTG curve of LNPs is less sharp and this observation illustrates a more moderate thermal degradation. This result is in accordance with the study by Nair et al, (2014), who obtained the nanosized lignin through mechanical shear treatment. Moreover, thermal analysis of pristine lignin and lignin nanoparticles by means of TGA confirmed that the treatment was successful for the complete removal of hemicellulose residual material, initially present in the raw material, as observed in FTIR spectra (Fig.…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…1a shows the TG and DTG curves of pristine lignin and LNPs: compared with pristine lignin, the DTG curve of LNPs is less sharp and this observation illustrates a more moderate thermal degradation. This result is in accordance with the study by Nair et al, (2014), who obtained the nanosized lignin through mechanical shear treatment. Moreover, thermal analysis of pristine lignin and lignin nanoparticles by means of TGA confirmed that the treatment was successful for the complete removal of hemicellulose residual material, initially present in the raw material, as observed in FTIR spectra (Fig.…”
Section: Resultssupporting
confidence: 95%
“…Del Saz-Orozco et al, (2012) also studied the reinforcement effect of lignin nanoparticles (softwood lignosulfonates) with an average diameter of 1.6 m, on the performance of phenolic foams, and the results showed that the compressive modulus and compressive strength increased 28 and 74%, respectively, compared to unreinforced foams, due to its good distribution. Nair et al (2014) and his co-workers investigated the size distribution of lignin particles mechanically sheared for different time periods. The results showed that welldistributed nanolignin particles (mainly 20-30 nm), obtained after 4 h of mechanical treatment, effectively increased the thermal stability of polyvinyl alcohol (PVA) when blended, in comparison to the original lignin/PVA composite.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, both DLNPs/PVA and OLNPs/PVA composites exhibited higher T i and T p . Such thermal stability improvement for other PVA-based nanocomposites has also been reported, which contain similar phenolic compound nanofillers such as melanin, polydopamine, and Kraft nanolignin particles prepared through high shear homogenization [10, 13, 33]. …”
Section: Resultsmentioning
confidence: 75%
“…Nair et al [92] used a simple mechanical homogenization method to create lignin nanoparticles. Softwood KL water dispersions at a concentration of 5 g/L were treated for up to 4 h with a high shear homogenizer at 15,000 rpm.…”
Section: Production Of Nano-/microsized Lignin Materialsmentioning
confidence: 99%